Effects of two aerobic exercise training protocols on parameters of oxidative stress in the blood and liver of obese rats - Delwing-de Lima D. (2018)
© 2017, The Physiological Society of Japan and Springer Japan KK, part of Springer Nature.We evaluated the effects of moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) protocols on the alterations in oxidative stress parameters caused by a high-fat diet (HFD), in the blood and liver of rats. The HFD enhanced thiobarbituric acid reactive substances (TBA-RS) and protein carbonyl content, while reducing total sulfhydryl content and catalase (CAT) and glutathione peroxidase (GSH-Px) activities in the blood. Both training protocols prevented an increase in TBA-RS and protein carbonyl content, and prevented a reduction in CAT. HIIT protocol enhanced SOD activity. In the liver, HFD didn’t alter TBA-RS, total sulfhydryl content or SOD, but increased protein carbonyl content and CAT and decreased GSH-Px. The exercise protocols prevented the increase in protein carbonyl content and the MICT protocol prevented an alteration in CAT. In conclusion, HFD elicits oxidative stress in the blood and liver and both protocols prevented most of the alterations in the oxidative stress parameters.